Model of banking system functioning - B. S. Boldin (Путеводитель предпринимателя)
In this article we provide a model of optimum banking system behavior using optimum management theory and also using econometric analysis of the movement of major types of financial instruments in banking system. This model successfully shows us reaction of banking system on such events as worlds financial crisis. Also here is a description of banking system functioning which is useful in more common econometrical model of balance.